EXPLORING BANANA PEEL EXTRACT AS A POTENTIAL TREATMENT FOR PERIODONTITIS: AN ANIMAL MODEL STUDY - Garcia, Maria; Lin, Chen (Ayden Journal of Drug and Pharmaceutical Research, 2024)
Periodontitis, characterized by inflammation in the periodontal tissues, is primarily driven by the interplay between bacterial pathogens and the host tissue. Key bacterial culprits in periodontal diseases include Porphyromonas gingivalis and Aggregatibacter actinomycetemcommitans, which release lipopolysaccharides (LPS) as toxins. LPS-induced destruction of periodontal tissues triggers the release of inflammatory cytokines like IL-1, IL-6, and TNF-α. The consequential tissue damage is a leading cause of tooth loss in adults, potentially impacting oral health-related quality of life. The initial treatment for periodontitis typically involves scaling and root planing, often complemented by adjuvant therapies like local hyaluronic acid gel application. These adjuvant therapies play a crucial role in promoting healing processes by exhibiting anti-inflammatory and antibacterial properties, while also stimulating cell growth. Periodontal tissue regeneration primarily relies on the migration of nearby stem cells to the damaged site, where they differentiate into specialized cells, ultimately replacing the damaged tissue. Understanding these mechanisms and therapies is vital for enhancing periodontitis treatment outcomes